In Vitro Mass Propagation of Ornamentally and Medicinally Important Coelogyne flaccida Lindl. through Pseudobulb Segments (Plant Tissue Culture and Biotechnology, 2013)
Regeneration competence of pseudobulb segments of Coelogyne flaccida, procured from in vitro grown cultures, was assessed in MS and Mitra (M) medium alone and in combinations with BA (4.44 ?M), Kn (5.65 ?M), NAA (5.37 ?M), and coconut water (CW 10%). Juvenility of the tissues, chemical stimulus, and position of the explants (apical/basal) were the key factors in initiating the response. The explants from pseudobulbs (>0.8 cm in length) did not regenerate whereas those from younger ones (